One-Level Lumbar Degenerative Spondylolisthesis and Posterior Approach: Is Transforaminal Lateral Interbody Fusion Mandatory?. Issue 8 (15th April 2017) - Challier, Vincent; Boissiere, Louis; Obeid, Ibrahim; Vital, Jean-Marc; Castelain, Jean-Etienne; Bénard, Antoine; Ong, Nathalie; Ghailane, Soufiane; Pointillart, Vincent; Mazas, Simon; Mariey, Rémi; Gille, Olivier
Abstract : Study Design: A monocentric open-label randomized controlled trial (MRCT). Objective: Comparison of clinical and radiological outcomes between isolated instrumented posterior fusion (PLF) and associated instrumented posterior fusion and interbody fusion by transforaminal approach (PLF + TLIF) for patients suffering from one-level lumbar degenerative spondylolisthesis (DS) undergoing surgery. Summary of Background Data: DS is a common cause of symptomatic lumbar stenosis. PLF has shown better clinical outcome than decompression with noninstrumented posterolateral fusion. TLIF with interbody cage showed better fusion rate than PLF. There is a need for randomized controlled trials to compare PLF with and without TLIF as to clinical and radiological outcomes. Methods: This is a MRCT comparing PLF and TLIF techniques in surgical treatment of DS. Sixty patients were included in a secured database from 2009 to 2011 and randomized into two groups: 30 PLF with posterior pedicle screws and intertransverse autologuous graft, and 30 TLIF in which an interbody fusion by transforaminal approach was added. Data included clinical (pain and disability), surgical (blood loss and operating time), and radiological (alignment and fusion) parameters at baseline and 2-year follow-up. Comparison was made by Student t test and Chi-square test. Results: There was a significant improvement in each group for pain and disability but no difference between the groups. Radiographic assessment showed better posterolateral fusion rate for TLIF without superiority in segmental lordosis improvement. A case of deformity cascade with spino-pelvic mismatch at baseline was noted in PLF. Conclusion: Posterior decompression and instrumented fusion is an efficient technique that proved its significant clinical benefit in the surgical treatment of DS. TLIF did not show its superiority neither in clinical nor alignment parameters despite a better fusion rate. These results suggest that TLIF is not mandatory in this specific indication. Sagittal alignment analysis by standing full-body images should be considered in DS care. Level of Evidence: 2